TEACHERS AND EDUCATION OF CHARACTER INSTILLATION (Research Result at Private Elementary School of Muhammadiyah in Medan) - Amini Amini Amini (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
Teachers are the most important element in the development of character education in elementary school, because it becomes the main foundation for a child. Therefore character education made a continuous process to produce a future human figure rooted in the cultural values of the Indonesian nation. Character education in the current context is very relevant to students to tackle the ongoing moral crisis in our country, including free association, crime against friends, teenage theft, cheating, drug abuse and drugs, pornography, brawls, and others. This is based on the results of research on SDS Muhammadiyah about teacher and character education education. The research methodology was conducted with qualitative descriptive analysis. Data obtained based on interviews, observation, and study documentation with the object of research. The result of the research shows that character education education in SDS Muhammadiyah 29 Medan City is contained in all subjects and outside subjects that are instilled early on by all teachers. Cultivation of character education conducted in all subjects through 3 content, ie general content (PAI, PKn, IPS, IPA, Bahasa Indonesia, Mathematics, Arts and Culture), special content (Kemuhammadiyahan), and Local Content (Malay Arabic / Arabic, English, Computer). Character education model performed outside the subjects through 4 things, namely: religious habituation (religious), discipline exercises, fun activities, and sports activities. Commonalities include (the implementation of Zuhr prayers bertamaaah, dhuha congregation, tadarus Al-Qur'an and memorizing the verses of Al-Qur'an, and culture shake). Discipline includes (the existence of rules and school rules and liaison books every day). Kewiraaan include (Flag ceremony and Hizbul wathan). Exercise includes (physical fitness exercise).